An extended food web from Greenland : adding birds, spiders and plants to a parasitoid-lepidopteran web - Hopkins, Tapani (Helsingfors universitet, 2012)
Quantitative food webs have been used since the 1990s to describe the ecology of ecosystems. Such webs describe not only 'who eats whom' but also how many individuals get eaten, giving a detailed picture of the connections in an ecosystem. This detail allows far-reaching ecological conclusions to be drawn, for all manner of questions ranging from the influence of abiotic and biotic factors on population dynamics to the effect of latitude on ecosystem structure. Currently the webs' greatest limitations are their incompleteness and lack of geographic coverage: most published webs focus on a tiny fragment of the total food web, and there are few webs from higher latitudes. In this thesis I address these limitations, by extending a parasitoid-lepidopteran web which is being collected in the High Arctic. I add data on bird and spider predation of the web's Lepidoptera, and on the lepidopterans' herbivory of their food plants. Specifically, I ask what the relative strengths of predation and parasitism are in this community, and what effect herbivory has on the plants' seed production. I measured predation rates using both live caterpillars and modelling clay dummies as bait. The former, caterpillars of Sympistis nigrita tethered to threads, gave an estimate of both spider and bird predation. The latter showed bird predation only, but gave a larger sample size than tethered caterpillars. For the herbivory rates, I measured the seed production of avens flowers (Dryas octopetala x integrifolia, one of the main lepidopteran food plants) when damaged by feeding caterpillars. I found that predation is an important cause of mortality for S. nigrita, comparable to the high rates of parasitism already observed. During the larval period, some 38% of S. nigrita caterpillars are killed by spiders, 8% by parasitoids and 8% by birds. The caterpillars ate highly variable amounts of avens flowers, with 14.4% of flowers damaged by feeding in a set of 743 flowers, and 8.3% in another set of 672 flowers. The damaged flowers produced ...